Fair Production and Allocation of an Excludable Nonrival Good. - Maniquet, François; Sprumont, Yves (Econometrica, 2004)
We study fairness in economies with one private good and one partially excludable nonrival good. A social ordering function determines for each profile of preferences an ordering of all conceivable allocations. We propose the following Free Lunch Aversion condition: if the private good contributions of two agents consuming the same quantity of the nonrival good have opposite signs, reducing that gap improves social welfare. This condition, combined with the more standard requirements of Unanimous Indifference and Responsiveness, delivers a form of welfare egalitarianism in which an agent's welfare is measured by the quantity of the nonrival good that, consumed at no cost, would leave her indifferent to the bundle she is assigned. Reprinted by permission of the publisher.